2007
DOI: 10.1017/s0022112007007021
|View full text |Cite
|
Sign up to set email alerts
|

Sedimenting sphere in a variable-gap Hele-Shaw cell

Abstract: We have measured the trajectory and visualized the wake of a single sphere falling in a fluid confined between two closely spaced glass plates (a Hele-Shaw cell). The position of a sedimenting sphere was measured to better than 0.001d, where d is the sphere diameter, for Reynolds numbers (based on the terminal velocity) between 20 and 330, for gaps between the plates ranging from 1.014d to 1.4d. For gaps in the range 1.01d-1.05d, the behaviour of the sedimenting sphere is found to be qualitatively similar to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
(50 reference statements)
0
2
0
Order By: Relevance
“…Given the results in [7] and the values of r = p ρ s /ρ 0 and St, our system straddles the boundary of the viscous and inertial regimes, in which the particles either reach the Stokes velocity or the inertial velocity, respectively. The Stokes velocity in our Hele-Shaw system is 0.75∆ρgd 2 sin θ/(18νρ 0 ) ⇡ 0.6m/s with the adjustment factor 0.75 from Lee et al [19] for the current Hele-Shaw cell of width 1.14d. (Wall effects are avoided in Courrech du Pont et al [7] because the tank width is larger than 15d.)…”
Section: Bed Activity and Beach Anglesmentioning
confidence: 99%
“…Given the results in [7] and the values of r = p ρ s /ρ 0 and St, our system straddles the boundary of the viscous and inertial regimes, in which the particles either reach the Stokes velocity or the inertial velocity, respectively. The Stokes velocity in our Hele-Shaw system is 0.75∆ρgd 2 sin θ/(18νρ 0 ) ⇡ 0.6m/s with the adjustment factor 0.75 from Lee et al [19] for the current Hele-Shaw cell of width 1.14d. (Wall effects are avoided in Courrech du Pont et al [7] because the tank width is larger than 15d.)…”
Section: Bed Activity and Beach Anglesmentioning
confidence: 99%
“…Hence, we chose the Hele-Shaw cell to have a gap width of 2l = 2 mm given available Gamma Alumina particles with diameter d = 1.75 ± 0.05 mm and effective density 2.08 ± 0.2g/cm 3 with water-filled pores. We note that Lee et al (2007) considered one particle settling in a Hele-Shaw cell, and observed quasi-two-dimensional behaviour for gap widths 2l < 1.05d, and three-dimensional behaviour for 2l > 1.1d. With our choice of 2l = 2 mm and d = 1.75 ± 0.05 mm, we are in a quasi-three-dimensional regime of particle settling.…”
Section: Validity Of Linear Momentum Dampingmentioning
confidence: 71%